(untitled) (International Journal of Environmental Sciences, 2025)
The study aimed to evaluate the recovery of degraded soils in former coca plantations and their economic valuation through the cultivation of Inga edulis "huaba" in Ricardo Palma - Tingo María. The study was applied, explanatory in nature, with a non-experimental design. The population under study consisted of degraded soils from former coca plantations in Ricardo Palma Tingo María, covering 4 hectares. A sample of degraded soils from former coca plantations planted with Inga edulis "huaba" aged 2, 4, and 6 years was defined, consisting of 12 plots of 100 m2 each. The technique employed was a survey, and the instrument was a questionnaire validated by experts. The results showed that after 4 years of planting Inga edulis in degraded soils, they have recovered to be used in sustainable agricultural activities, and that the economic value at market prices is increasing due to the contribution of macro and micronutrients, which showed significant differences the planting time, which leads to the conclusion that Inga edulis restores degraded soils by providing macro and micronutrients and its economic value is related to the planting time).